Synthesis of Cu-Doped Ti-Containing MCM-41 and its Photocatalytic Performance for Indoor Air Purification - Qiu, J.P.; Wang, D.; He, Z.Q.; Song, S. (Asian Journal of Chemistry, 2014)
The prepared catalysts were synthesized in a mild way and characterized by various analytical instruments including X-ray diffraction, nitrogen physisorption, UV-visible spectroscopy, high resolution-transmission electron microscopy and X-ray photoelectron spectroscopy. All samples exhibited the typical mesoporous structure and spherical structure. Copper and titanium species in the MCM-41 support were well anchored on the mesoporous framework in the form of metal oxides. The adsorption tests for formaldehyde examined the positive effect of metal incorporation. In the static state test, MCM-41 adsorbed 31 % of formaldehyde and Ti/Cu-MCM-41 elevated this value to 41 %. Moreover, Ti/Cu-MCM-41 demonstrated the superior photocatalytic performance under both UV- and visible-light irradiation, achiveing 57 % and 18 % of formaldehyde degradation at the end of reaction, respectively. With the X-ray photoelectron spectroscopy and UV-Visible results, an intense interaction between Ti and Cu was observed and the synergy effect mechanism in the bimetallic catalyst was proposed.